Addressing the moral hazard through explicit deposit insurance : a comparative appraisal of the Kenya Deposit Insurance Act 2012 - Van Heerden, C.M. (Corlia) (University of Pretoria, 2019)
Thesis (LLD)--University of Pretoria, 2019.